Pulmonary disease in hamsters infected with Leptospira interrogans: Histopathologic findings and cytokine mRNA expressions - Marinho, Márcia [UNESP]; Oliveira-Júnior, Itamar Souza [UNESP]; Monteiro, Cristina Maria Rodrigues [UNESP]; Perri, Silvia Helena [UNESP]; Salomão, Reinaldo [UNESP] (American Society of Tropical Medicine and Hygiene, 2009)
Our aim was to evaluate the pulmonary changes induced by Leptospira interrogans infection in hamsters, and the gene expression of endogenous mediators in lung fragments during 28 days of observation. The animals were euthanized on days 4, 7, 14, 21, and 28 post-inoculation. Histopathologic lung analysis showed hemorrhage, pneumonia, alveolar congestion, and infiltrated cellular areas, with increasing severity until day 21 post-inoculation. Tumor necrosis factor (TNF)-α mRNA expression enhanced in first days with peak on day 4 and slightly decreased in the final phase. The interleukin (IL)-10 remained relatively constant throughout the period, with the exceptions of days 4 and 14. The endothelial nitric-oxide synthesis (eNOS) showed an increased expression on day 4, followed by an augment on days 7 and 14, and remaining constant up to day 28 post-infection. Our results demonstrate that inoculation of L. interrogans sorovar Icterohaemorrhagiae induced pulmonary lesions, including pulmonary hemorrhage, supporting that the lung is a target organ. Copyright © 2009 by The American Society of Tropical Medicine and Hygiene.